2020
DOI: 10.2478/hjbpa-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Are Fiscal Deficits Really Inflationary? An Investigation Into Ethiopia’s Experience

Abstract: This study establishes long-run relations between budget deficits and inflation, while controlling for money supply owing to the justified links between deficits and money supply especially for developing countries. We employed time series data with temporal coverage of 1980-2018. Augmented Dickey Fuller has tested nonstationary for all series, but with all stationary at first difference. The Engle-Granger (1981) methodology for Cointegration tested long-run relation between budget deficits, money supply and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These stimuli were mainly financed through public borrowing (Heitzig et al, 2021). Numerous studies have analyzed the relationship between fiscal deficit financing and inflation (see (Alemu, 2020;Ekinci, 2016;Fasanya, Fajobi, & Adetokunbo, 2021;Sethi, Bhujabal, Das, & Sucharita, 2019;Yien, Abdullah, & Azam, 2017)). It is still an open debate on which mode of deficit financing causes more macroeconomic instability especially inflation than the other.…”
Section: Stylized Facts On Fiscal Deficit and Inflation In Sub-sahara...mentioning
confidence: 99%
“…These stimuli were mainly financed through public borrowing (Heitzig et al, 2021). Numerous studies have analyzed the relationship between fiscal deficit financing and inflation (see (Alemu, 2020;Ekinci, 2016;Fasanya, Fajobi, & Adetokunbo, 2021;Sethi, Bhujabal, Das, & Sucharita, 2019;Yien, Abdullah, & Azam, 2017)). It is still an open debate on which mode of deficit financing causes more macroeconomic instability especially inflation than the other.…”
Section: Stylized Facts On Fiscal Deficit and Inflation In Sub-sahara...mentioning
confidence: 99%
“…The Ethiopian water body could support a yield of 94,000 tons of fish per year, indicating substantial contribution to food security and income generation (Deng, 2020). Coincident with the potential volume of fishery resources, there is a need to enhance fish consumption habit and improve the quality of available fishery products (Alemu and Adesina, 2016;Yilma et al, 2020). It is evidenced that the annual per capita consumption of fish was 240 g/person which is less than 10% of fish consumption in East African sub-region (MOA, 2002;Tesfaye and Wolff, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the frequency and preference of Non-sensory factors (risk perception, behaviour, personal attributes and beliefs) as well as sensory elements (texture, taste, smell, freshness) may influence food preferences, including fish (Honkanen et al, 2005). Moreover, it is reported that fish consumption in Ethiopia is limited due to lack of interest, lack of availability, fear of spoilage, religious matter and lack of habit of consumption (Alemu and Adesina, 2016). Fish consumption, production, and export could all be improved by implementing practical and long-term plans to solve linked obstacle factors in one's own country (Supartini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%